Urban Management Tools to Support Better Dwelling Conditions to Immigrants - Emília Malcata Rebelo (2004)
The main goal of this paper consists in presenting an interactive and integrated set of strategic planning and urban management tools, designed to monitor the evolution of dwelling variables, and support political decisions on urban regeneration issues, favouring economic and social integration of immigrants and ethnic minority groups. A set of tableaux de bord in the Porto Municipality concerning immigrant dwelling location and characteristics is developed (at the parish level), as a case study. Conclusions and recommendations are extracted from this research.